2015
DOI: 10.1080/02650533.2015.1013526
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Child Protection Error in Social Work: Towards a Holistic-Rational Perspective

Abstract: Social work in the United Kingdom remains embroiled in concerns about child protection error. The serious injury or death of vulnerable children continues to evince much consternation in the public and private spheres. Governmental responses to these concerns invariably draw on technocratic solutions involving more procedures, case management systems, information technology and bureaucratic regulation. Such solutions flow from an implicit use of instrumental rationality based on a 'means-end' logic. While brin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…In the naturalist decision-making approach, paying attention to both the intuitive thinking that professionals use in practice and the organisational and contextual elements in which such decisions occur is essential. Currently, there is also a strong plea for the introduction of a holistic-rational perspective in which professionals consider the emotional elements elicited when issuing judgements and decisions, which can be quite useful for assessing risk in different situations (Houston, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the naturalist decision-making approach, paying attention to both the intuitive thinking that professionals use in practice and the organisational and contextual elements in which such decisions occur is essential. Currently, there is also a strong plea for the introduction of a holistic-rational perspective in which professionals consider the emotional elements elicited when issuing judgements and decisions, which can be quite useful for assessing risk in different situations (Houston, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Rationality pressures make managers prioritize productivity where the discretionary power of streetlevel bureaucrats suffers [6,7]. Houston [24] argues that rationality objectives emphasize efficiency excessively on behalf of the quality of service delivery.…”
Section: Contextual Factorsmentioning
confidence: 99%
“…Wider trends in managing child protection systems have sought to address the challenges of this work through a burgeoning administrative structure focused on technocratic solutions (Houston, 2015). Mirroring this trend, solutions to the problem of communication failures between processionals contributing to the deaths of children in care have tended to focus on the technical transfer of information, instituting tools to support this purpose (Department for Health and Social Security, 1982;Department of Health, 1991 ;Laming, 2003;Reder & Duncan, 2013).…”
Section: Interprofessional Workingmentioning
confidence: 99%
“…Mirroring this trend, solutions to the problem of communication failures between processionals contributing to the deaths of children in care have tended to focus on the technical transfer of information, instituting tools to support this purpose (Department for Health and Social Security, 1982;Department of Health, 1991 ;Laming, 2003;Reder & Duncan, 2013). Tools may include, for example, procedure manuals, assessment frameworks and decision making tools (Hall & Slembrouck, 2007;Houston, 2015;Munro, 2011;Reder & Duncan, 2003). Research in child protection systems (Munro, 2011) as well as other high-risk industries (Sidney Dekker, Hollnagel, Woods, & Cook, 2008) has demonstrated that an overreliance on a technocratic approach may not only be ineffective in securing a safer system, but may also produce unwanted consequences.…”
Section: Interprofessional Workingmentioning
confidence: 99%
See 1 more Smart Citation